Processing fluency for visual synchrony perception - Bamford, JS; Tarr, B; Cohen, E (PsyArXiv, 2022)
Prior research has found that interpersonal synchrony increases social closeness and cooperation: this is often referred to as the synchrony-bonding effect. Most explanations for this synchrony-bonding effect rely upon higher-order social cognition (e.g. shared goals or selfother merging). Relatively little attention has been given to the perceptual experience of synchrony, and the low-level perceptual mechanisms involved, such as processing fluency. In two pre-registered experiments, we tested the novel hypothesis that synchrony (congruent movement) is easier to process than non-synchrony. In Study 1, no effect of direction congruency on performance was detected. However, Study 2 found a significant effect of speed congruency. This indicates decreased processing load when stimuli are moving at the same speed. We then discuss how these reduced visual stimuli may relate to naturalistic periodic movement. Crucially, the effect observed here does not rely upon social stimuli and may operate at an early stage of perceptual processing. This is an initial step in establishing a novel theory of the synchrony-bonding effect, based upon the principles of processing fluency.